Smart Polymer Nanocomposites Energy Harvesting, Self-Healing and Shape Memory Applications - Ponnamma, Deepalekshmi; Sadasivuni, Kishor Kumar; Cabibihan, John-John; Al-Maadeed, Mariam Al-Ali (Springer Series on Polymer and Composite Materials,, 2017)
This book covers smart polymer nanocomposites with perspectives for application in energy harvesting, as self-healing materials, or shape memory materials. The book is application-oriented and describes different types of polymer nanocomposites, such as elastomeric composites, thermoplastic composites, or conductive polymer composites. It outlines their potential for applications, which would meet some of the most important challenges nowadays: for harvesting energy, as materials with the capacity to self-heal, or as materials memorizing a given shape. The book brings together these different applications for the first time in one single platform. Chapters are ordered both by the type of composites and by the target applications. Readers will thus find a good overview, facilitating a comparison of the different smart materials and their applications. The book will appeal to scientists in the fields of chemistry, material science and engineering, but also to technologists and physicists, from graduate student level to researcher and professional. .